2015
DOI: 10.1111/jon.12239
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Contrast‐Enhanced Perfusion MRI and Diffusion‐Weighted Imaging in Grading of Gliomas

Abstract: Purpose Accurate glioma grading is crucial for treatment planning and predicting prognosis. We performed a quantitative volumetric analysis to assess the diagnostic accuracy of histogram analysis of diffusion-weighted imaging (DWI) and dynamic contrast-enhanced (DCE) T1-weighted perfusion imaging in the preoperative evaluation of gliomas. Methods Sixty-three consecutive patients with pathologically-confirmed gliomas who underwent baseline DWI and DCE-MRI were enrolled. The patients were classified by histopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
55
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 20 publications
8
55
1
2
Order By: Relevance
“…The Spearman test demonstrated that the K trans of tumours shows positive correlation with clinical stage. These were in concordance with many other studies on other tumours in vivo, such as breast cancer (26) and glioma (27).…”
Section: Discussionsupporting
confidence: 93%
“…The Spearman test demonstrated that the K trans of tumours shows positive correlation with clinical stage. These were in concordance with many other studies on other tumours in vivo, such as breast cancer (26) and glioma (27).…”
Section: Discussionsupporting
confidence: 93%
“…These two parameters have already been shown to be different between grade III and IV [12, 16], between HGGs and LGGs [12, 1416, 50], and between grade II and III oligodendrogliomas [54]. In our study, k ep_90 was also significantly lower in grade IV gliomas.…”
Section: Discussionsupporting
confidence: 67%
“…Vajapeyam et al [8] , in their recently published study, reported higher K trans and K ep values and lower V e values in higher-grade pediatric tumors. Our results differ from the results of previous DCE perfusion studies as we found no signifi-cant differences in the permeability measurements of low-and high-grade neoplasms [9,10,12,14] . However, when we compared the kinetic parameters of pilocytic astrocytomas with those of high-grade posterior fossa tumors like medulloblastoma, we found higher leakage and V e values in pilocytic tumors.…”
Section: Discussioncontrasting
confidence: 57%
“…Dynamic contrast-enhanced (DCE) perfusion is another exogenous contrast-based perfusion technique that has been used for the evaluation of brain tumors in adult patients [10][11][12] . There are a few DCE-based perfusion studies on tumor assessment in pediatric patients [8,13] .…”
mentioning
confidence: 99%